ANALISIS KOHESI DAN KOHERENSI DALAM WACANA MAJALAH ELSHINTA.COM PADA BERITA TOL BAKAUHENI-TERBANGGI BESAR SUDAH SIAP BEROPERASI 24 JAM - Hafiidha Sari, Raras; Rahayu, Titin (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to describe the result of cohesion and coherence analysis as well as the latest news discourse on elshinta.com on Saturday 11 May 2019 in the reporting of the Bakauheni Toll Road Big Tol Ready to Operate 24 Hours. The method used in this study is descriptive, namely describing the result of the analysis found in this study. Thid type of research is qualitative research data is news that has been transcribed. The technique used to extract data is the note and technique of note taking. As for the data analysis technique used ini this study are based on dance theory, namely a complete and higest language above a sentence or clause with high cohesion that is continuous and has a final beginning andhas been manifestly conveyed trough oral and written. The result of the study are the: 1) use of cohesion and; 2) the use of coherence. Cohesion is a way that composes discourse into the from of interrelationships berween sentences or one component in a solid and intact manner. Element of cohension winch includes references subsituas, ellipses, conjunctions, and lexical cohension which include repetition synonyms, antonyms, colloquies, hyponyms, equivalence. While coherence is the compilation of content in the discourse element as a semantic organization, which uses ideas in the logical sequence to achieve the intended speech correctly